1987
DOI: 10.1210/endo-120-6-2453
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Isomer of 2-Hydroxymelatonin: A Novel Metabolite of Melatonin*

Abstract: A previously unknown melatonin metabolite was isolated by chloroform extraction and reverse phase HPLC from human and rat urine after administration of synthetic melatonin and characterized by mass spectroscopy and proton magnetic resonance spectroscopy to 1-acetyl-1,2,3,3a,8,8a-hexahydro-8a-hydroxy-5-methoxypyrrolo[2,3-b ]indole, a cyclic isomer of 2-hydroxymelatonin. This isolation was based on the fact that our melatonin antibody (a-MT-K1) cross-reacted against this novel metabolite at a level of 0.1% (mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
5
18
0
Order By: Relevance
“…In previous studies concerning the metabolic fate of MT, various metabolites of MT have been identified in urine [32,33]. In rats and rabbits, aMT6s (55-80%) and glucuronide 6-OHMT (5-30%) were found to be excreted into urine.…”
Section: Relationship Between Tod and Mt Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies concerning the metabolic fate of MT, various metabolites of MT have been identified in urine [32,33]. In rats and rabbits, aMT6s (55-80%) and glucuronide 6-OHMT (5-30%) were found to be excreted into urine.…”
Section: Relationship Between Tod and Mt Contentsmentioning
confidence: 99%
“…Also NAS, which is the nearest precursor of MT and excreted as glucuronide and sulfate conjugates, is a minor metabolite of MT (< 2% of urinary metabolites), and the proportion of NAS to 6-OHMT ranged from 9 to 21%, with a mean of 15% in humans [34]. Free 6-OHMT (< 2% of urinary metabolites) in rat urine, 1--4% in humans, 5-methoxy-3-indoleacetic acid (< 2%), and cyclic 2-hydroxy-MT have also been reported [33].…”
Section: Relationship Between Tod and Mt Contentsmentioning
confidence: 99%
“…Since only small amounts of II and III were formed, an additional BP-induced pathway of melatonin catabolism is suggested. Microsomal oxidation at carbon 2 is a possibility as there is a recent report identifying a cyclic isomer of 2-hydroxymelatonin as a novel urinary metabolite of melatonin (13). On the other hand, oxidation may have occurred elsewhere in the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In the past fifteen years, understanding the diverse physiologic roles of melatonin has increased greatly and it is now known to have anti-oxidant properties. A cyclic isomer of melatonin, 1-acetyl-1,2,3,3a,8,8a-hexahydro-8a-hydroxy-5-methoxypyrrolo [2,3-b]indole, was isolated from urine from mice and humans and characterized by electron impact MS and NMR [63]. Subsequent research by Tan and coworkers employing 2-D NMR and semi-empirical calculations refined the initially proposed structure to 1-acetyl-1,2,3,3a,8,8a-hexahydro-3a-hydroxy-5-methoxy-pyr-rolo [2,3-b]indole (61), differing from the first structure in the position of the hydroxyl group (3a vs. 8a) [64].…”
Section: Melatoninmentioning
confidence: 99%
“…The first hydroxyl radical reacts with the indole ring in melatonin resulting in a carbon-centered radical (62) that subsequently reacts with the side-chain nitrogen to give the cyclic radical (63). A second hydroxy radical converts (63) to (61) with concomitant formation of water. In a mouse study, (61) was present largely as a sulfate conjugate [65].…”
Section: Melatoninmentioning
confidence: 99%